1959
DOI: 10.1530/acta.0.xxxii0233
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogenic Activity at Menopausal Age in Women With Diabetes Mellitus (»diabète Gras«)

Abstract: A cytological investigation has been made into the occurrence of oestrogenic effects in female diabetic patients of menopausal age. A significant difference from a control group in the frequency of oestrogenic smears has been found. This difference is attributed to the diabetic patients with obesity and/or hypertension. The signs of oestrus are shown to be probably of adrenal origin. The possible significance of this with regard to the hereditary and environmental aspects of endometrial cancer is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1964
1964
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The combination of obesity and hypertension, however, is strikingly different in this regard, being associated with a definite impairment of glucose tolerance. The breast cancer women differ from essentially normal women in 2 respects: (I) in normal women the maximum blood glucose value is reached after 30 minutes, whereas in breast cancer patients this occurs after 60 minutes; (2) at least 2% hours are needed for this. These features are noted even in breast cancer patients without obesity or hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of obesity and hypertension, however, is strikingly different in this regard, being associated with a definite impairment of glucose tolerance. The breast cancer women differ from essentially normal women in 2 respects: (I) in normal women the maximum blood glucose value is reached after 30 minutes, whereas in breast cancer patients this occurs after 60 minutes; (2) at least 2% hours are needed for this. These features are noted even in breast cancer patients without obesity or hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we had found by means of endocrine cytology that among postmenopausal women there was an increased frequency of karyopycnotic (" estrogenic ") smears in those who were obese, hypertensive and diabetic (de Waard and Baanders, 1961 ;de Waard and Oettle, 1965). Since these estrogens originated outside the ovaries (Bruinsma and de Waard, 1959) we felt confident that they were synthetized as such in the adrenal cortex. Subsequently, it was found that only the precursors of extra-ovarian estrogens are synthetized in the adrenal cortex; the conversion of androstenedione to estrogens (mainly estrone) takes place in peripheral tissues ( MacDonald et a/., 1969;Poortman et al, 1973) inter alia in adipose tissue (Schindler et al, 1972).…”
mentioning
confidence: 99%
“…d) It decreased in obese women when they succeeded in achieving significant weight loss [10]. e) The stimulus was of extra-ovarian, most probably of adrenal origin [10,11].…”
Section: Postmenopausal Oestrogen Production Related To Obesitymentioning
confidence: 99%